Implementation of Tax Administration of Income Tax Article 21, Unified Income Tax, and VAT at the General Bureau of the Regional Secretariat of Banten Province - Siti Ainaya Fatimah (Journal of Practical Management Studies, 2026)
The implementation of tax administration in government institutions plays an important role in supporting transparent, accountable, and compliant state financial management in accordance with prevailing tax regulations. Every transaction related to payments to employees and third parties has the potential to generate tax obligations that must be properly managed through an orderly, systematic, and well-integrated administrative system. This study aims to analyze the implementation of tax administration, including Income Tax (PPh) Article 21, Unified Income Tax, and Value Added Tax (VAT) at the General Bureau of the Regional Secretariat of Banten Province. This research employs a qualitative approach with a descriptive method to describe actual conditions and identify various constraints encountered in the overall implementation of tax administration. Data collection techniques include observation, interviews, and documentation involving parties responsible for tax management. The results indicate that tax administration has been carried out through stages of calculation, withholding or collection, payment, and reporting in accordance with applicable regulations. The implementation of an electronic-based tax administration system has significantly improved efficiency, accuracy, and administrative order. However, several challenges remain, including dynamic changes in tax regulations and the need for high accuracy in the continuous tax data input process within government institutions